An investigation of the temporal induction of cytokine mRNAs in LPS-challenged thioglycollate-elicited murine peritoneal macrophages using the reverse transcription polymerase chain reaction - Simpson, A. E. C. M.; Tomkins, P. T.; Cooper, K. L. (Inflammation research, 1997)
A comprehensive study to standardise interleukin (IL)-1 alpha, -1 beta, -6, -10, -12 and tumour necrosis factor alpha (TNF alpha) mRNA detection in murine peritoneal macrophages, using the reverse transcription polymerase chain reaction (RT-PCR) was carried out. Thioglycollate-elicited peritoneal exudate cells were harvested from female BALB/c mice and the adherent macrophage fraction isolated for use. Peritoneal macrophages (1 x 10(6)) were incubated in the presence or absence of lipopolysaccharide (LPS; at a final concentration of 1 microgram/ml) for 0, 1, 2, 3, 4, 5 and 24 h. Culture supernatants and cells were harvested at each time point, the secreted cytokine protein levels quantified by sandwich immunoassays and the cytokine mRNA levels assessed by RT-PCR. The IL-6 mRNA was not expressed in detectable amounts in the macrophages, unless challenged with LPS. TNF alpha, IL-1 alpha, IL-1 beta, IL-10 and IL-12 mRNAs were expressed in both stimulated and unstimulated macrophages. The levels of the PCR products and thus mRNAs of all the cytokines increased with LPS stimulation, maximal levels being achieved 3 to 5 h post stimulation. RT-PCR produced consistent results, indicating that this technique could be used to investigate the effect of biological mediators and novel pharmacological agents on cytokine mRNA levels in macrophages.